Crushing Modes of Aluminium Tubes under Axial Compression using Finite Element Analysis - Ghazali, N.D.; Said, M.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Nowadays, aluminium tubes have been used widely as a controlled absorption of kinetic crash energy. The energy absorption process is subjected to axial loading is based on the formation of plastic folds. A numerical study of the crushing of aluminium circular tubes has been carried out to investigate their buckling behaviors under axial compression and to predict the energy absorbed by the tube. Circular tube with diameter 25.4 mm, height 25.4 mm and thickness 0.29 mm is compressed axially with velocity 5 mm/min using ABAQUS/CAE 2016 between two rigid platen. Typical deformation mode is studied and presented. Mixed mode has been deformed because of the ratio of the wall thickness, diameter and the length of the tubes. These approved that geometry of the tube influence the deformation mode as well as the energy absorbs by the tube.